The Relationship Of Physical Activity Levels To The Sleep Quality Of Sport Science Students - Sheva Risetya Al Lukman; Sri Sumartiningsih (Universitas Negeri Semarang, 2026)
Physical activity and sleep quality are important factors that influence students' health and academic performance. Final-year students often face academic demands that may affect both aspects. This study aimed to analyze the relationship between physical activity level and sleep quality among final-year students of the Sport Science Study Program, Faculty of Sport Science, Universitas Negeri Semarang. This research employed a quantitative cross-sectional design involving 40 respondents selected through purposive sampling. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Spearman Rank correlation test. The results showed that 50% of respondents had high physical activity levels, 32.5% had moderate levels, and 17.5% had low levels. The majority of respondents experienced poor sleep quality (95%). The Spearman Rank test revealed a correlation coefficient of ρ = 0.044 with a significance value of p = 0.786 (p > 0.05). These findings indicate that there is no significant relationship between physical activity level and sleep quality among final-year students of the Sport Science Study Program. Sleep quality is likely influenced by factors other than physical activity.